2013
DOI: 10.1603/en12243
|View full text |Cite
|
Sign up to set email alerts
|

Wind-Borne Dispersal of a Parasitoid: the Process, the Model, and its Validation

Abstract: The aphelinid parasitoid Eretmocerus hayati Zolnerowich & Rose (Hymenoptera: Aphelinidae) was recently released in Australia as a biocontrol agent against the crop pest Bemisia tabaci Gennadius (Hemiptera: Aleyrodidae). It was found that the parasitoid can spread over several kilometers in a single generation and continue laying eggs for over a fortnight. A simple wind-advection model was fitted to emergence data from a first release between Fassifern and Kalbar, Queensland, and its predictive ability was test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…This could be due to differences in methodology as Adashkevich et al (1986) investigated H. hebetor dispersal after only 6 days of observations while in the present study H. hebetor dispersal was monitored for 5 weeks. Moreover, as reported in other settings, parasitoid species dispersal distance could be influenced by weather, especially temperature (Fahrner, Lelito, & Aukema, 2015;Yu et al, 2009), wind (Desouhant, Driessen, Lapchin, Wielaard, & Bernstein, 2003;Kristensen, Schellhorn, Hulthen, Howie, & Barro, 2013;Messing, Klungness, & Purcell, 1994) and landscape (Josso et al, 2013).…”
Section: Discussionmentioning
confidence: 67%
“…This could be due to differences in methodology as Adashkevich et al (1986) investigated H. hebetor dispersal after only 6 days of observations while in the present study H. hebetor dispersal was monitored for 5 weeks. Moreover, as reported in other settings, parasitoid species dispersal distance could be influenced by weather, especially temperature (Fahrner, Lelito, & Aukema, 2015;Yu et al, 2009), wind (Desouhant, Driessen, Lapchin, Wielaard, & Bernstein, 2003;Kristensen, Schellhorn, Hulthen, Howie, & Barro, 2013;Messing, Klungness, & Purcell, 1994) and landscape (Josso et al, 2013).…”
Section: Discussionmentioning
confidence: 67%
“…[28]). In the previous study [25], a parameter specifying the maximum wind speed at which flights occurred was found to be a key parameter determining fit between the model and data.…”
Section: Methodsmentioning
confidence: 99%
“…To model the number of parasitized hosts present in each field at collection time, we assumed that time from oviposition to emergence was 19 -25 days, distributed approximately according to a truncated normal distribution with variance of 2 days. Although the literature on laboratory observed times often suggests a shorter period [30,31], the field data observed by Kristensen et al necessitated the use of this longer time distribution [7,25] based on the number of emergences observed at longer times from collection. The mean number of collected parasitized hosts could then be calculated based on the population density history and the probability of collection in each field.…”
Section: Bayesian Modelling Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The model simulations indicated that peak densities of MEAM1 B. tabaci were higher for low or non-suitable crops than for crops with a medium suitability. This counter-intuitive result was explained by the fact that medium suitability winter crops supported high parasitoid ( Eretmocerus hayati ) populations, which can suppress B. tabaci populations in summer crops (De Barro, 2012; Kristensen et al , 2013). Therefore, both the surrounding landscape and crop rotation choices had a significant effect on simulated B. tabaci population dynamics.…”
Section: Biotic Factorsmentioning
confidence: 99%